nterleukin (IL)-4-independent induction of immunoglobulin (Ig)E, and perturbation of T cell development in transgenic mice expressing IL-13 - Emson,CL; Bell,SE; Jones,A; Wisden,W; McKenzie,AN (J Exp Med, 1998)
Recent studies using interleukin (IL)-4-deficient animals have highlighted the existence of IL-4-independent immunoglobulin (Ig)E induction. We have established transgenic mice expressing IL-13 from a transgene comprising a genomic fragment containing the IL-13 gene and the human CD2 locus control region. The transgenes were expressed in lymphoid tissues and induced by T cell activators, suggesting regulation by elements of the IL-13 promoter. IL-13 transgenic lines expressed 10-100-fold higher levels of serum IgE than their littermate controls, but had normal levels of other serum Ig isotypes. Elevated IgE levels were also detected in sera from IL-4-deficient mice carrying IL-13 transgenes, indicating that IL-4 is not required for IL-13-induced IgE expression in the mouse. Expression of IL-13 also perturbed the development of thymocytes. Although thymocyte development was normal up to 4 wk of age, thymocyte number decreased dramatically thereafter, reaching 10% of normal by 10 wk, and despite normal size and appearance, histological examination demonstrated that transgenic thymi contained only small foci of thymocytes. The reduction in thymocyte number was due mainly to a depletion of CD4(+)CD8(+) thymocytes, and did not affect significantly the composition of peripheral T cell populations. These data indicate that expression of IL-13 transgenes in vivo can regulate IgE production in the mouse, and that IL-13 may also influence thymocyte development.